The influence of Socialized Tuition Fee Assistance Program on the Academic Performance of WVSU-IICT graduating students AY 2006-2007 - Quicoy, Rosalie; Dumpit, Duvince Zhalimar; Presaldo, Jay; de la Peña. Sharone; Eucogcan, Jessica
The Socialized Tuition Fee Assistance Program (STFAP) is a university financial assistance given to qualified and deserving students which involve tuition and laboratory fee discounts. Students are assessed of their bracket assignments based on their annual family income. Brackets 1-4 are paying subsidized or discounted tuition fees from 0-75% while brackets 5-9 are paying 100-200% tuition fees. In effect brackets 6-9 are subsidizing the tuition fees of students in brackets 1-4. The aim of the study was to determine the influence of STFAP on the academic performance f WVSU-IICT graduating students in terms of grade-point-average, awards and co-curricular involvement. It also tried to evaluate specifically on the program implementation, delivery of benefits and monitoring of the set of rules and procedures. In addition, it will give management the information in making policy decisions of the program. The study was limited to WVSU-IICT graduating students who are grantees of STFAP. It used the purposive smapling from the total of 67 graduating students of IICT only 51 are STFAP beneficiaries. The graduating students for the school year 2006-2007 from the Institute f Information and Communications Technology (IICT) were chosen as the respondents. The respondents were composed of 17 males and 34 females. The subject comprised approximately 20% of the total IICT students and 2% of the total WVSU population. The study used frequency counts and percentages on the responses of the respondents concerning the screening procedures and benefits derived from STFAP. The inferential statistics used the T-test to determine the test for independence of the variables and descriptive correlation specifically, the Pearson Product Moment Correlation to look for a relationship between STFAP brackets and academic performance. Both inferential statistics set at -05 alpha levels. Additional data and information were gathered through a focused group discussion of the grantees' perception on STFAP. The results of the study revealed the grantees were satisfied of the benefits received but there is a need to improve the monitoring and evaluation of the program. some however, were not motivated due to lack of emphasis on the GPA requirement and absence of incentives to academic awardees. generally, the management of the program which includes implementation, granting of benefits and monitoring of the program is very satisfactory. In terms of awareness of the program, accessibility of application forms and assistance provided to the applicants, these aspects were properly managed. Some areas however need improvement like the accessibility of the forms. The program is weak in terms of monitoring and validation procedures. The implementation of the minimum grade-point-average (GPA) set by the committee was not implemented and the only consideration for evaluation is the gross annual income of the family. some grantees were recipient of the academic awards and distinctions, members of various university-wide organizations and actively participated in various co-curricular activities. Based on the results of the inferential statistics,there was no significant difference between the grade point average of grantees belonging to brackets 1-4 and those in brackets 5-9. Specifically, the benefits given to brackets 1-4 did not to a great extend enhance their academic performance. Hence, STFAP Bracketing and STFAP in general have no significant influence on the academic performance of IICT graduating students. Recommendations were made to improve the STFAP program implementation bu cnducting an extensive program review.